Mixed vs full donor engraftment early after hematopoietic cell transplant: Impact on incidence and control of cytomegalovirus infection. Issue 3 (29th March 2019) - Green, Jaime S.; Shanley, Ryan M.; Brunstein, Claudio G.; Young, Jo‐Anne H.; Verneris, Michael R.
Abstract: Recovery of cytomegalovirus (CMV)‐specific immunity after hematopoietic cell transplantation (HCT) is essential in controlling CMV infection. We hypothesize that mixed donor engraftment as measured by chimerism at day 30 in CMV D(+) HCTs and full chimerism in CMV D(−) HCTs will be predictive of CMV reactivation. Prospectively collected data for 407 CMV R+ HCT recipients transplanted from 2006 to 2014 at the University of Minnesota were retrospectively analyzed. Full and mixed donor engraftment were defined as ≥95% or <95% donor cells at day 30, respectively. Source of engraftment determination included preferentially peripheral blood CD3 fraction, then myeloid cell fraction (CD15+), then bone marrow. In 407 CMV R+ subjects, 77% (n = 313) were CMV D(−) cells from umbilical cord blood (n = 209), peripheral blood (n = 58) or marrow (n = 46). Fifty three per cent received reduced intensity conditioning (RIC). At day +30, full donor engraftment was seen in 82% of myeloablative and 55% of RIC transplants. The cumulative incidence of CMV infection 1‐year after transplant was not different in patients with full (54%, n = 276) or mixed (53%, n = 131) donor engraftment. Control of CMV did not significantly differ among the two groups. In multiple regression analysis, there was no significant association between donor engraftment (mixed or full) and incidence or control of CMV.